Pendekatan Bimbingan dan Konseling dalam Pendampingan Emosional Siswa Autis: Studi Kasus di SKH Negeri 02 Kota Serang - Adhwa Kayla Safitri; Yahdinil Firda Nadira (STKIP Subang, 2026)
This study aims to describe the emotional support provided by Guidance and Counseling (BK) teachers to autistic students at SKH Negeri 02 Kota Serang. Autistic children often experience difficulties in communication, emotional expression, and behavior regulation, requiring flexible and individualized support. Using a descriptive qualitative method, the study found that the BK teacher builds an empathetic relationship, creates an emotionally safe space, and uses calm communication and stimulus redirection when signs of emotional instability appear. Music activities and play are also utilized to reduce tension and improve the student’s focus, supported by consistent routines and positive reinforcement. This form of emotional support helps students better regulate their emotions, follow instructions, and interact more adaptively. The findings highlight the importance of humanistic and responsive approaches in counseling services for autistic students in special education settings.